Comparative analysis of aroma substances of vanilla co-fermented black tea. Issue 4 (February 2021) - Wu, Juxian; Wu, Xiaorong; Yuan, Guoan; Chen, Xuexun; Shi, Xiaoyan; Chen, Haibing; Huang, Baiqi
Abstract: Different tea-making processes are different, and the aroma substances and main components of the tea-like products are different. The types of aromas and tastes of tea after processing are different. Vanilla, like tea, needs to be fermented and processed before it presents an attractive milk flavor. Based on the co-fermentation process of vanilla and tea, this study developed co-fermented black tea, and compared the aroma and content analysis of ordinary black tea and co-fermented black tea. The results showed that the special aroma substances of co-fermented vanilla black tea contained 2, 3-dihydro-2, 2, 6-trimethylbenzaldehyde (0.42%); GermacreneD (1.54%); 3, 7, 11 -Trimethyl-1, 6, 10-dodecantrien-3-ol acetate (0.28%). It is a new type of mixed black tea product with richer ingredients and unique aroma.